Validitas Digital Signature Dalam Smart Contract Terhadap Jual Beli Produk Hasil Pertanian Digital - Kusuma, Ajeng Pramesthy Hardiani; Jasmine, Maysha Aulia (Acten Journal Law Review, 2025)
Developments in information technology have changed the way transactions are conducted in agribusiness, one of which is the implementation of smart contracts and digital signatures for the sale and purchase of digital agricultural products. This study aims to examine the validity and legal standing of Smart Contracts and Digital Signatures according to contract law in Indonesia. This study uses a normative method, with a conceptual approach and legal regulations. In this study, something has been found that can show Digital signatures in smart contracts have a valid legal status provided that they meet the provisions stipulated in applicable regulations. In particular, the rules in the ITE Law and PP 71/2019, which provide a strong legal basis for the recognition of digital signatures as a means of authentication in electronic contracts. The implications of digital agricultural product trading practices, by utilizing this technology, have the potential to accelerate transactions, increase efficiency, and provide legal certainty, especially the rights and obligations of the parties concerned. However, support is needed in the form of more detailed technical regulations, education on law and digital for agricultural business actors, and equitable infrastructure development to ensure that the digital transformation in agribusiness is legally valid and fair in its implementation.